Implementing Problem-based Learning to Develop Students' Critical and Creative Thinking Skills - Ida Ayu Made Sri Widiastuti; Ida Bagus Nyoman Mantra; IGA Lokita Purnamika Utami; Ni Luh Sukanadi; I Nyoman Adi Susrawan (Jurnal Pendidikan Indonesia, 2023)
Problem-Based Learning (PBL) is an innovative approach to education that exposes students to real-life problems, promoting critical thinking, problem-solving, and teamwork through practical methods. This study analyzes the effectiveness of Problem-based learning (PBL) in improving students' critical and creative skills. Problem-based learning (PBL) is a student-centered pedagogy that focuses on developing critical and creative skills. This study used a descriptive research design to gather the phenomena of implementing Problem-Based Learning in the classroom. The data were collected by conducting interviews and questionnaires to the students who were selected as the sample in this study and semi-structured interviews with the selected teachers. The questionnaire showed that there were 59.10% of strongly agreed responses; 38.97% of agreed responses; 1.93% of the undecided; responses and none of the responses showed disagreed and disagreed. The study results showed that Problem-Based Learning is an effective teaching method to improve creative thinking skills and student learning outcomes. This study implies that teachers should increase the implementation of Problem-Based Learning to help students develop critical and creative thinking skills.